Determinan Penanaman Modal Dalam Negeri Di Provinsi Jambi “Pendekatan Error Correction Model” - Tania Putri; Haryadi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to identify and analyze the extent to which Interest Rates, Inflation, Economic Growth, and Rubber Exports influence Domestic Investment (PMDN) in Jambi Province. This research is a descriptive study using a quantitative approach. The data used are time series data from 1997 to 2023 obtained from BPS (Statistics Indonesia) and Bank Indonesia. The analytical method employed in this study is the Error Correction Model (ECM). Based on the results of the analysis, the findings indicate that in the short term, Interest Rates have a positive and significant effect, while Economic Growth has a negative and significant effect. Meanwhile, Inflation and Rubber Exports show a negative but insignificant effect on Domestic Investment. In the long term, Interest Rates and Economic Growth exhibit a negative and insignificant effect, while Inflation and Rubber Exports also show a negative and insignificant effect on Domestic Investment.